Εντοπισμός του προβλήματος της αστικοποίησης στην Κύπρο. Λύσεις στο πρόβλημα και εφαρμογές τους - Σιταρένος, Παύλος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The present work aims at identifying the problem of urbanization in Cyprus, examining the methodology followed and applying statistical analysis of the result. To achieve this goal, this work involves a combination of research methods. Specifically, the methodology applied was remote sensing through satellite images and processing them in two satellite image processing software such as ERDAS and ENVI. The result of the above treatment was so important that the scholar tried to solve the problem of urbanization by applying energy efficient cities in Cyprus without rejecting the local plans implemented in Cyprus. Also, this research is also supported by Cyprus University of Technology’s (EXCELSIOR) questionnaire, aimed at exploring the need and use of Earth Observation Data in Cyprus. The questionnaire was given to several public services and private companies where the main result was that they do not know specialized enough software and programs for the remote sensing for the Earth, which can make their day-to-day workplace easier. This study is active in Limassol due to the fact that sales of residential or commercial real estate in the last two years have risen sharply in this area. Also, because of what is a model, it could not be applied to all of Cyprus unless it is judged sustainable.
Keywords: Urbanization; Cyprus; Satellite images; Image processing; ERDAS; ENVI; Αστικοποίηση; Κύπρος; Τηλεπισκόπηση